ANALISIS PENGARUH KOMPENSASI EKSEKUTIF, KEPEMILIKAN SAHAM EKSEKUTIF DAN PREFERENSI RISIKO EKSEKUTIF TERHADAP PENGHINDARAN PAJAK PERUSAHAAN - Umi Hanafi; Puji Harto (Diponegoro Journal of Accounting, 2014)
This study aim to obtain empirical evidence about the influence of executive compensation, executive ownership and  risk preference of executive to corporate tax avoidane. The population of this study was al companies listed in Indonesian Stock Exchange in 2010-2012. Sample consists of companies in property, real estate and building construction. This sector chosen because of high growth in that sector than any business sector such as plantation and mining. The growth of property, real estate and building construction industry also increases, 29% in 2010 increased to 32% in 2011 and 51% in 2012. But the growth is not followed by increased effective taxes rate. Effective taxes rate amounting to 29% in 2010 decreased to 27% in 2012. Hypothesis testing used multiple regression analysis with dummy variables. The result of this study show that executive compensation and executive ownership have significant and posisitive effect on tax avoidance. Executive who have the risk preference of risk taker also have significantly positive on tax avoidance.